Knowledge, attitude and practices towards cervical cancer control among University students in Kilimanjaro region, Tanzania. - Alex Mremi; Aron P Joseph; Donatila V Njunwa; Doris A Ntupwa; Doris G Rwenyagila; Joseph Mlay (PLoS ONE)
Background Cervical cancer (CC) is a major public health issue in the sub-Saharan Africa region, partly due to limited public awareness among women at risk. University students are part of the age group that is at risk. Assessing their knowledge, attitude, and practices (KAP) about CC, its causes, and prevention methods can reveal gaps that need to be addressed through education. We aimed to assess KAP towards CC control and their determinants among University students in Tanzania. Methods A cross-sectional survey was conducted among 708 undergraduate students in three Universities, using a pre-tested questionnaire. Descriptive statistics and binary logistic regression were used to describe variables and identify associations between variables; a p-value of <0.5 determined the association. Results The majority of students (75.7%) were not knowledgeable, and 82.5% had a negative attitudes regarding CC. Only 25.4% had ever been screened against CC. Being female and a medical student in ≥4th year of studying were significantly associated with good knowledge and attitude of CC (p < 0.000), while other socio-demographic characteristics didn't show any association. Conclusion The findings indicate that Tanzanian University students' lack the basic knowledge and attitudes towards CC prevention and control, highlighting the need for comprehensive strategies to ensure no woman is left behind.